RIPHeart (Remote Ischemic Preconditioning for Heart Surgery) Study: Myocardial Dysfunction, Postoperative Neurocognitive Dysfunction, and 1 Year Follow‐Up. Issue 7 (26th March 2018) - Meybohm, Patrick; Kohlhaas, Madeline; Stoppe, Christian; Gruenewald, Matthias; Renner, Jochen; Bein, Berthold; Albrecht, Martin; Cremer, Jochen; Coburn, Mark; Schaelte, Gereon; Boening, Andreas; Niemann, Bernd; et al.
Abstract : Background: Remote ischemic preconditioning (RIPC) has been suggested to protect against certain forms of organ injury after cardiac surgery. Previously, we reported the main results of RIPHeart (Remote Ischemic Preconditioning for Heart Surgery) Study, a multicenter trial randomizing 1403 cardiac surgery patients receiving either RIPC or sham‐RIPC. Methods and Results: In this follow‐up paper, we present 1‐year follow‐up of the composite primary end point and its individual components (all‐cause mortality, myocardial infarction, stroke and acute renal failure), in a sub‐group of patients, intraoperative myocardial dysfunction assessed by transesophageal echocardiography and the incidence of postoperative neurocognitive dysfunction 5 to 7 days and 3 months after surgery. RIPC neither showed any beneficial effect on the 1‐year composite primary end point (RIPC versus sham‐RIPC 16.4% versus 16.9%) and its individual components (all‐cause mortality [3.4% versus 2.5%], myocardial infarction [7.0% versus 9.4%], stroke [2.2% versus 3.1%], acute renal failure [7.0% versus 5.7%]) nor improved intraoperative myocardial dysfunction or incidence of postoperative neurocognitive dysfunction 5 to 7 days (67 [47.5%] versus 71 [53.8%] patients) and 3 months after surgery (17 [27.9%] versus 18 [27.7%] patients), respectively. Conclusions: Similar to our main study, RIPC had no effect on intraoperative myocardial dysfunction, neurocognitive function and long‐term outcome in cardiac surgery patients undergoing propofol anesthesia. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01067703.